O constructo economia plural nos estudos relacionados com a economia solidária: revisão sistemática no período 2000-2016 - Suzana Melissa de Moura Mafra da Silva; Washington José de Souza; Ana Paula Borba Costa (Ciências Sociais Unisinos)
This text brings results of a qualitative research, carried out from an approach of systematic review of the literature on academic production regarding plural economics, having as reference the use of the plural economy construct in national and international scientific texts, available in the Portal de Periódicos Capes. The study takes into account the period from 2000 (the year of the first academic production) to 2016. The search generated 112 occurrences by using the terms “Economia Plural”; “Plural Economy”; “Economia Solidária”; “Solidary Economy”; and “Outra Economia”. For the treatment of the information collected, the following inclusion and exclusion criteria were applied - articles published in the period from 2000 to 2016, originals and published in periodicals (peer review), and studies that relate simultaneously the themes of plural economy and solidarity economy -, which resulted in 19 articles for further analysis. The recurrence of a multidimensional view attributed to the construct plural economy, when used in studies in the field of the economy of solidarity, goes beyond the field of Economy, reaching Philosophy and Political Science when they consider, respectively, the biases of the substantive rationality and new institutional configurations.